Complement Activation in Patients With Heat-Related Illnesses: Soluble CD59 Is a Novel Biomarker Indicating Severity of Heat-Related Illnesses - Yuki Nakamura, MD; Koichiro Sueyoshi, MD, PhD; Yukari Miyoshi, MD, PhD; Tadashi Ishihara, MD, PhD; Yohei Hirano, MD, PhD; Yutaka Kondo, MD, PhD; Yoko Kuroda, BSc; Kazuhisa Iwabuchi, PhD; Ken Okamoto, MD, PhD; Hiroshi Tanaka, MD, PhD (Critical Care Explorations, 2022)
OBJECTIVES:. Although multiple organ dysfunction syndrome (MODS) is the main cause of death in patients with heat-related illnesses, its underlying pathophysiological mechanism remains elusive. Complement activation is considered one of the main causes of MODS in patients with sepsis and trauma. Considering the pathophysiological similarity of heat related-illnesses with sepsis and trauma, the complement system might be activated in patients with heat-related illnesses as well. Our aim was to investigate whether excessive complement activation occurs in patients with heat-related illnesses. DESIGN:. Prospective observational study. SETTING:. Emergency department in the university hospital. PATIENTS:. Thirty-two patients with heat-related illnesses and 15 age-matched healthy controls were enrolled in this study. INTERVENTIONS:. Blood samples were collected from the study subjects for the measurement of complement factors. MEASUREMENTS AND MAIN RESULTS:. Complement component 3a (C3a), complement component 5a (C5a), C5b-9, complement factor B (Ba), Factor H, and soluble CD59 in plasma were measured. The levels of C3a, C5a, C5b-9, and Ba significantly increased in patients with heat-related illnesses on day 0 compared with those in the healthy controls. Soluble CD59 was significantly high in patients with heat-related illnesses on day 0 and showed a correlation with the severity of the condition (Acute Physiology and Chronic Health Evaluation II, Sequential Organ Failure Assessment, and staging scores), Japanese Association for Acute Medicine disseminated intravascular coagulation scores, and the coagulation system (prothrombin time and fibrin degradation products). CONCLUSIONS:. The complement system was activated in patients with heat-related illnesses, suggesting that it is one of the causes of MODS. Soluble CD59 may be a potent biomarker for the severity of heat-related illnesses.